Repetitive Mechanical Recycling of Post-Consumer High Impact Polystyrene from Yogurt Cups: A Pilot-Scale Performance Assessment at Different Reprocessing Cycles - Guarda-Moraga, A; Valenzuela-Bascunan, X; Galotto-Lopez, M; Garrido-Ayala, L; Velasquez, E; Catalan-Gamonal, L (Elsevier B.V., 2024)
International legislation requests to increase recycling rates of plastic waste towards a circular economy. Nowadays, high impact polystyrene from yogurt cups is not recycled on a commercial scale and research gaps need to be addressed. In this research, mechanical recycling of post-consumer yogurt cups was carried out at a pilot scale. The variation of the physical-mechanical properties and overall migration of the post-consumer plastic to food simulants as a function of re-extrusion cycles were evaluated to test its suitability for the manufacture of new yogurt packaging. The performance of the post-consumer plastic was highly deteriorated when the recycling cycles advanced. Among the most important consequences of reprocessing is that the impact strength and rigidity were significantly reduced. Besides, the overall migration measured by total immersion of post-consumer plastic into food simulants exceeded the limit established by the European legislation to be in contact with food and drastically increased with repetitive recycling. © 2023 The Author(s)